1989
DOI: 10.1111/j.1365-2125.1989.tb03444.x
|View full text |Cite
|
Sign up to set email alerts
|

The renal and haemodynamic effects of a 10 h infusion of glutamyl‐L‐ dopa in normal man.

Abstract: The Royal Infirmary, Edinburgh EH3 9YW 1 y-L-glutamyl-L-dopa (gludopa) and placebo were given by intravenous infusion to 12 healthy salt replete men for 10 h in a single-blind randomised fashion. 2 Gludopa caused a cumulative natriuresis of 46.5 mmol compared with placebo with a biphasic pattern and this was associated with a small reduction in body weight. 3 A small fall in arterial blood pressure and rise in pulse rate was seen with gludopa. 4 Plasma renin activity, atrial natriuretic peptide and urine kalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Wilk et al, 1978;Lee, 1987;Jeffrey et al, 1988a,b;MacDonald et al, 1989;Cummings et al, 1990). Dopamine concentrations following gludopa administration were found to be much higher in the kidney than in mouse heart (Wilk et al, 1978) or rat liver (Cummings et al, 1990).…”
Section: Glycerol-induced Arfmentioning
confidence: 99%
“…Wilk et al, 1978;Lee, 1987;Jeffrey et al, 1988a,b;MacDonald et al, 1989;Cummings et al, 1990). Dopamine concentrations following gludopa administration were found to be much higher in the kidney than in mouse heart (Wilk et al, 1978) or rat liver (Cummings et al, 1990).…”
Section: Glycerol-induced Arfmentioning
confidence: 99%
“…Alternatively, the PRA-lowering effect is mediated centrally; the renin suppressing activity of L-dopa has been suggested to originate from CNS activity (9,15). At variance with the data discussed so far is a recent study on gludopa by MacDonald et al (78): a 10-h infusion at 25 pg/kg/min into healthy volunteers showed no effect on PRA. However, in that study the effects on natriuresis and urine volumes were also different from generally observed effects.…”
Section: Gludopamentioning
confidence: 67%
“…The results suggest that DA, formed in the kidney locally from L-dopa, reaches inhibitory but not excitatory DA receptors at the juxtaglomerular cells or that it reaches excitatory receptors at not sufficiently high levels to stimulate them. Plasma DA levels during gludopa infusion are low in comparison to the levels obtained during DA infusion: -4.5 nmol/L with gludopa 25 pg/kg/min (78), and 240 nmol/L with DA 3 pg/kg/min (51). Alternatively, the PRA-lowering effect is mediated centrally; the renin suppressing activity of L-dopa has been suggested to originate from CNS activity (9,15).…”
Section: Gludopamentioning
confidence: 96%
“…y-GT will cleave the y-glutamyl moieties of gludopa and glu-5-HTP releasing the free amino acid precursors, L-dopa and L-5-HTP respectively, in relatively high quantities on both sides of the proximal tubular cells for subsequent decarboxylation. The enzyme has a tremendous capacity to metabolize y-glutamyl compounds, as shown by the very low recovery of unmetabolized gludopa in the urine (~1 % ) after its intravenous infusion in man [27,341. Administration of the two glutamyl compounds therefore offers the possibility of investigating whether there is competition between L-dopa and 5-HTP for renal LAAD in vivo in man.…”
Section: Discussionmentioning
confidence: 99%